Tricky Topology: Persistence of Folded Human Telomeric i-Motif DNA at Ambient Temperature and Neutral pH - Abdelhamid, Mahmoud A. S.; Waller, Zoë A. E. (Frontiers in Chemistry, 2020)
i-Motifs are four-stranded DNA structures formed from sequences rich in cytosine, held together by hemi-protonated cytosine-cytosine base pairs. These structures have previously been utilised extensively as pH-switches in DNA-based nanotechnology. Recently there has been an increasing interest in i-motif structures in biology, fuelled by examples of when these can form under neutral conditions. Herein we describe a cautionary tale regarding handling of i-motif samples. Using CD and UV spectroscopy we show that it is important to be consistent in annealing i-motif DNA samples as at neutral pH, i-motif unfolding kinetics is dependent on the time allowed for annealing and equilibration. We have found that the quadruplex structure formed by the human telomeric i motif sequence surprisingly persists at neutral pH and ambient temperature; conditions where it was previously assumed to exist predominantly as a random coil. This study has implications not only for work with i-motif DNA structures, but also in the uses and applications of these in nanotechnological devices.